Effects of methane seepage activity on the morphology and geochemistry of authigenic pyrite. (November 2021) - Miao, Xiaoming; Feng, Xiuli; Liu, Xiting; Li, Jingrui; Wei, Jiangong
Abstract: As an important product of methane seepage, pyrite contains abundant methane seepage information. It is right that the formation mechanisms of authigenic pyrite at methane seepage is still not so clear. We aim to reveal the importance of authigenic pyrite in methane seepage activity through different analytical methods. To this end, the morphological and geochemical characteristics of pyrite in a core obtained from the 'Haima seep' sedimentary area were analyzed. The results show that compared with pyrite formed under normal marine sedimentary environments, the pyrite content, degree of pyritization, and sulfur isotope value are higher in the sulfate-methane transition zone (SMTZ), and pyrite has larger mean diameters and standard deviations. These geochemical anomalies suggest four major changes in methane flux at site Q6, focusing anaerobic oxidation of methane (AOM) for extended periods of time in four subsequent layers termed paleo-SMTZ. Here, changes in methane flux to the SMTZ is mainly due to dissociation of subsurface methane hydrates. Therefore, this study can help us better understand the formation of pyrite under methane seepage activity and provide a scientific basis for identification of methane seepage activity. Highlights: We identified three methane release events in Q6 and identified specific horizon of methane seepage. The sulfur isotope of pyrite are significantly higher in the horizon of methane seepage. Anaerobic oxidation of methane can also change the iron speciation and significantly increase pyrite iron/highly reactive iron. Pyrite mainly consists of framboids (mean diameter > 20 μm, standard deviation > 3 μm) in the horizon of methane seepage.